2023
DOI: 10.3389/fpls.2023.1112214
|View full text |Cite
|
Sign up to set email alerts
|

Grapevine genome analysis demonstrates the role of gene copy number variation in the formation of monoterpenes

Abstract: Volatile organic compounds such as terpenes influence the quality parameters of grapevine through their contribution to the flavour and aroma profile of berries. Biosynthesis of volatile organic compounds in grapevine is relatively complex and controlled by multiple genes, the majority of which are unknown or uncharacterised. To identify the genomic regions that associate with modulation of these compounds in grapevine berries, volatile metabolic data generated via GC-MS from a grapevine mapping population was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…listed in Table 2 . A few studies have uncovered new genes and rare alleles that regulate secondary metabolites associated with color and flavor [ 46 , 49 , 165 ], pathogen resistance [ 43 , 47 , 56 , 79 , 145 , 165 , 166 , 167 ], and abiotic stress tolerance [ 41 , 42 , 55 ]. These findings foster an understanding of the genetic basis of diverse traits in domesticated crops and offer promising prospects for introducing candidate genes (for disease resistance and quality traits) through molecular breeding or precise genome editing into elite cultivars.…”
Section: Plant Pan-genomics-driven Insights For Understanding the Bas...mentioning
confidence: 99%
See 1 more Smart Citation
“…listed in Table 2 . A few studies have uncovered new genes and rare alleles that regulate secondary metabolites associated with color and flavor [ 46 , 49 , 165 ], pathogen resistance [ 43 , 47 , 56 , 79 , 145 , 165 , 166 , 167 ], and abiotic stress tolerance [ 41 , 42 , 55 ]. These findings foster an understanding of the genetic basis of diverse traits in domesticated crops and offer promising prospects for introducing candidate genes (for disease resistance and quality traits) through molecular breeding or precise genome editing into elite cultivars.…”
Section: Plant Pan-genomics-driven Insights For Understanding the Bas...mentioning
confidence: 99%
“…Thus, the availability of plant pan-genomes allows researchers and breeders to explore important candidate genes for improving crop yield, nutritional quality, and adaptability to changing climatic conditions and diseases. For instance, a few comparative genomic studies have revealed that gene amplification plays a vital role in disease resistance, abiotic stress tolerance, and other agronomic traits associated with plant development, architecture, and yield [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. In addition, the high-quality pan-genomes also make it possible to study previously inaccessible regions of the eukaryotic genomes, including centromeres, long heterochromatic blocks, rDNA regions, etc., that exhibit low recombination, and provide new insights into crop genome evolution [ 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…Genomics data may further advance tropical fruit flavour through targeted breeding and genetic selection strategies or gene-editing technology (Mathiazhagan et al 2021 ). Genome-wide association studies (GWAS) and quantitative trait loci (QTL) mapping approaches have previously identified genome regions responsible for the regulation of fruit flavour compounds in tomato (Gai et al 2023 ; Sapkota et al 2023 ), grape (Koyama et al 2022 ; Bosman et al 2023 ) and apple (Yang et al 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the availability of plant pan-genomes allows researchers and breeders to explore important candidate genes for improving crop yield, nutritional quality, and adaptability to changing climatic conditions and diseases. For instance, a few comparative genomic studies have revealed that gene amplification plays a vital role in disease resistance, abiotic stress tolerance, and other agronomic traits associated with plant development, architecture, and yield [40][41][42][43][44][45][46][47][48][49]. In addition, the highquality pan-genomes also make it possible to study previously inaccessible regions of the eukaryotic genomes, including centromeres, long heterochromatic blocks, rDNA regions, etc., that exhibit low recombination, and provide new insights into crop genome evolution [50].…”
Section: Introductionmentioning
confidence: 99%